ADVANCED EXPERIENCE OF IMPLEMENTATION OF THE POLLING PROCEDURE WITH THE USE OF THE POLYGRAPH IN THE ACTIVITIES OF FOREIGN COUNTRIES FORCE STRUCTURES - Тракалюк, О.; Кузьменко, М.; Зубовський, Д. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article deals with the experience of the survey using the polygraph. Most of the focus is on the advanced experience of foreign countries force structures. The analysis indicates the existence of significant differences in the survey using the polygraph as in the practical sphere and in ensuring legal procedures. Obtained results should be used in national practice. Keywords: a survey using the polygraph, advanced experience, foreign countries force structures